Implementation of Puzzle Picture Media Improves Learning Outcomes of Science Student's in Class V of SD Negeri Kuta Rentang - Norhazaruddin, Nurul Fatehah Binti; Filina, Nurul Zikri (Teunuleh Publisher, 2023)
This study aims to improve student learning outcomes through the application of puzzle picture media, especially in science learning for grade V of Kuta Rentang Elementary School. The type of research used in this study is Classroom Action Research with a Qualitative approach. The process of data collection, researchers use instruments, namely observation, tests, and documentation. The results of classroom action research and the discussion that have been presented, it can be concluded that science learning using puzzle media can improve the learning outcomes of grade V students of Kuta Rentang Elementary School, student learning outcomes in cycle I were 56% and in cycle II became 81% in cycle II and increased by 35% and has met the target set, namely 70% of students who have completed learning at the end of the cycle.